Clinical efficacy of xenon versus propofol: A systematic review and meta-analysis. Issue 20 (May 2018) - Xia, Yimeng; Fang, Hongwei; Xu, Jindong; Jia, Chenfei; Tao, Guorong; Yu, Buwei
Abstract: Background: Interest in the anesthetic use of xenon, a noble gas, has waxed and waned for decades, and the clinical effects of xenon are still debated. We performed a meta-analysis to compare the clinical efficacy of xenon with that of propofol. Methods: Electronic searches were performed through December 2017 using various databases, including PubMed, Embase, and the Cochrane Library. We identified thirteen trials that included a total of 817 patients. Results: Patients treated with xenon had a lower bispectral index (BIS) (weighted mean difference (WMD): −6.26, 95% confidence interval (CI): −11.33 to −1.18, P = .02), a higher mean arterial blood pressure (MAP) (WMD: 7.00, 95% CI: 2.32–11.68, P = .003) and a lower heart rate (HR) (WMD: −9.45, 95% CI: −12.28 to −6.63, P < 0.00001) than propofol-treated patients. However, there were no significant differences between the 2 treatment groups in the effects of nondepolarizing muscular relaxants, the duration spent in the postanesthesia care unit (PACU) (WMD: −0.94, 95% CI: −8.79–6.91, P = .81), or the incidence of perioperative complications [assessed using the outcomes of postoperative nausea and vomiting (PONV) (relative risk (RR): 2.01, 95% CI: 0.79–5.11, P = .14), hypotension (RR: 0.62, 95% CI: 0.27 to 1.40, P = .25), hypertension (RR: 1.27, 95% CI: 0.73–2.21, P = .39) and bradycardia (RR: 1.00, 95% CI: 0.36–2.74, P = 1.00)]. Conclusion: In this meta-analysis of randomized controlled trials, we found that xenon treatment resulted in a higher MAP, a lower HR, and a smaller BIS index than treatment with propofol.